Peran Komunikasi Keluarga terhadap Motivasi Belajar Anak Studi di Desa Keruak Kecamatan Keruak Kabupaten Lombok Timur Nusa Tenggara Barat - Jamiluddin Jamiluddin (LP2M STIT Palapa Nusantara, 2016)
The family is home education or soialisasi first and foremost is also a basic foundation for the child. Then it is appropriate that parents build communication with her children, because with good communication will affect child development optimally. The purpose of this research is to know the child's learning and motivation to learn the role of family communication against child learning motivation in the Keruak Sub-district Keruak. In this study, researchers used a purposive sampling. As for the method used in this research is descriptive qualitative approach with qualitative and data collection techniques through observation, interview and documentation. The results of this study showed that the level of motivation of a child to learn is still very low. This has resulted in many children only credentials that school, but children do not get a science at all. Low motivation of children in the study because (1) the socio-cultural Factors (2) Factors (3) Economic factors of parent education (4) environmental factors. So to resolve problems that occur in children's learning motivation are low, it is the role of parents is required in order to be able to communicate well with her children including through the involvement of parents in the learning activities in school and in the home and crucially namely provision of learning facilities are mainly guidance and impetus (motivation).